Near‐Infrared Organic Single‐Crystal Lasers with Polymorphism‐Dependent Excited State Intramolecular Proton Transfer. Issue 12 (8th May 2017) - Wang, Xuedong; Li, Zhi‐Zhou; Li, Shi‐Feng; Li, Hui; Chen, Jianwei; Wu, Yishi; Fu, Hongbing
Abstract : Organic solid‐state lasers (OSSLs) are broadly tunable coherent sources, potentially compact, convenient, and manufactured at low costs. As compared with conventional organic materials, organic molecules with excited state intramolecular proton‐transfer (ESIPT) process are excellent active laser medium candidates due to their inherent four‐level system. This study demonstrates the effect of the polymorphism‐dependent ESIPT on the OSSLs. It is found the α‐phase crystals with a low photoluminescence quantum efficiency of ≈2% emit two components: the tautomer A emissions and the tautomer B emissions, which indicate the noncomplete ESIPT case. For comparison, the β‐phase crystals with moderate intramolecular hydrogen‐bonding emitting near‐infrared photoluminescence have all tautomer B emissions, which are of relatively high photoluminescence quantum efficiency (≈15%) and are red‐shifted by an average of ≈250 nm from the corresponding absorptions. The complete ESIPT process of the β‐phase crystals contributes to the amplified spontaneous near‐infrared emission (λ ≈ 730 nm) with a low threshold of ≈1.86 µJ cm −2 . This work has provided the platform for the investigation of the ESIPT lasers, which contributes to the high‐performance organic solid‐state near‐infrared laser devices. Abstract : Excited‐state intramolecular proton‐transfer (ESIPT)‐active organic molecules are excellent active laser medium candidates due to their inherent four‐level system. The complete ESIPT process of the β‐phase crystals can explain the amplified spontaneous emission at near‐infrared (NIR) wavelength, which contributes to the development of organic solid‐state NIR laser devices.